Harmonizing Islamic Values with Modern Urban Design: Privacy, Technology, and Cultural Preservation in Southeast Asian Architecture - Latif, Sahabuddin (Journal of Islamic Architecture, 2025)
Rapid urbanization in predominantly Muslim regions of Southeast Asia has significantly altered architectural design, shifting from privacy-oriented spatial layouts—such as courtyards and mashrabiyas—to open-plan urban models. This study examines the integration of Islamic values, particularly privacy and culturally sensitive spatial organization, into contemporary urban planning. By conducting a narrative literature review (NLR) of academic research, policy documents, and case studies, this research explores the impact of modernization on privacy considerations within Islamic architecture. The findings reveal the dual impact of surveillance technologies and smart systems, which enhance security but also pose risks to privacy. This study highlights the tension between privacy-conscious spatial organization and the increasing presence of digital monitoring systems in urban settings. The proposed framework promotes a balanced approach through zoning strategies, community engagement, and sustainable architectural solutions that preserve cultural identity while accommodating modernization. By integrating established privacy-oriented design principles with contemporary urban planning, this research provides valuable insights for policymakers and architects in designing inclusive and socially responsive environments. However, as this study relies on secondary sources, future research should incorporate empirical studies, including fieldwork and community engagement, to develop context-specific strategies. Comparative analyses across diverse socio-political settings will further clarify how different urban policies support or challenge the preservation of Islamic architectural values in contemporary cityscapes.